When Everyone Works Harder for Fewer Rewards, Is It Fair? Implications of "Organization-Wide Hardship" for Managing and Studying Organizational Fairness. Issue 2 (April 2019) - Levi, Ariel; Shapiro, Debra L.; Fried, Yitzhak; Markoczy, Livia; Noghani, Farzaneh
As organizations compete in an increasingly global and challenging environment, "working" often requires working harder for fewer rewards. In this article, we introduce the concept of "organization-wide hardship, " which refers to workforce-shared hardship that results from an organization's pursuit of a strategy associated with its industry-positioning goals. We propose a model for predicting and explaining employees' reactions to organization-wide hardship. Our analysis and model make several contributions to the justice literature. First, we highlight the importance of organization-wide hardship (associated with pay freezes or pay cuts, increased working hours, or reduced work–family balance) as a potential contributor to the experience of low fairness for all employees in the organization. Second, we argue that research on the effects of management accounts (explanations) for their decisions should be extended by considering the effects of accounts from nonmanagement sources. Third, we highlight the potentially paradoxical effects of providing external (rather than internal) accounts to employees as these likely heighten the hardship's perceived fairness yet also heighten employees' concern for their organization's future and hence their intended or actual turnover. Fourth, our article's theorizing adds a temporal (future-oriented) perspective to the largely past-oriented perspective of organizational justice–related theorizing and research. We discuss the implications of our model for organizations and leaders and scholars who aim to study employees' reactions to organization-wide hardship.